The polyketide synthase OsPKS2 is essential for pollen exine and Ubisch body patterning in rice. Issue 9 (8th September 2017) - Zhu, Xiaolei; Yu, Jing; Shi, Jianxin; Tohge, Takayuki; Fernie, Alisdair R.; Meir, Sagit; Aharoni, Asaph; Xu, Dawei; Zhang, Dabing; Liang, Wanqi
Abstract: Lipid and phenolic metabolism are important for pollen exine formation. In Arabidopsis, polyketide synthases (PKSs) are essential for both sporopollenin biosynthesis and exine formation. Here, we characterized the role of a polyketide synthase (OsPKS2) in male reproduction of rice ( Oryza sativa ). Recombinant OsPKS2 catalyzed the condensation of fatty acyl‐CoA with malonyl‐CoA to generate triketide and tetraketide α‐pyrones, the main components of pollen exine. Indeed, the ospks2 mutant had defective exine patterning and was male sterile. However, the mutant showed no significant reduction in sporopollenin accumulation. Compared with the WT (wild type), ospks2 displayed unconfined and amorphous tectum and nexine layers in the exine, and less organized Ubisch bodies. Like the pksb/lap5 mutant of the Arabidopsis ortholog, ospks2 showed broad alterations in the profiles of anther‐related phenolic compounds. However, unlike pksb/lap5, in which most detected phenolics were substantially decreased, ospks2 accumulated higher levels of phenolics. Based on these results and our observation that OsPKS2 is unable to fully restore the exine defects in the pksb/lap5, we propose that PKS proteins have functionally diversified during evolution. Collectively, our results suggest that PKSs represent a conserved and diversified biochemical pathway for anther and pollen development in higher plants. Abstract : The pollen exine is sculptured in a genetically determined manner, but the mechanism controlling exine pattern formation remains unclear. This study demonstrated that a rice polyketide synthase OsPKS2 plays an important role in exine patterning. Mutation in OsPKS2 leads to dramatic changes in pollen exine morphology but does not significantly affect sporopollenin production.